2011
DOI: 10.1007/s12564-011-9169-6
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization of American English native speaker norms: a case study of an English language classroom in South Korea

Abstract: This case study aims to reveal how conceptualization of native speakership was constructed and reinforced in a South Korean university classroom of English as a foreign language (EFL). In addition, it examines how this conceptualization positions native speakers, a nonnative EFL teacher, and learners, and what learning opportunities were provided in this classroom. The participants of the study were one instructor and his students. The data include classroom observations, interviews with the teacher and studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The first factor, American English exposure, expressed the greater use of the facilities associated with American English accent and revealed that those who prefer the American English accent over British are exposed more to the American facilities. This confirms both Kung and Wang (2018) and Ahn's (2011) study considering the fact that the proponents of this accent have been exposed to American English accents more than the other varieties and that they rarely experience listening to other varieties. Students` lack of exposure toward other varieties of English is also confirmed by Billiris (2011).…”
Section: Discussionsupporting
confidence: 84%
“…The first factor, American English exposure, expressed the greater use of the facilities associated with American English accent and revealed that those who prefer the American English accent over British are exposed more to the American facilities. This confirms both Kung and Wang (2018) and Ahn's (2011) study considering the fact that the proponents of this accent have been exposed to American English accents more than the other varieties and that they rarely experience listening to other varieties. Students` lack of exposure toward other varieties of English is also confirmed by Billiris (2011).…”
Section: Discussionsupporting
confidence: 84%
“…By extension, school textbooks are artifacts of that management because they are preceded by the adjective "school" (Curdt-Christiansen & Weninger, 2015), which validates the social norms they project. In the context of the present study, the unquestioned use of EFL textbooks and the lack of critical attention to their multimodal contents is problematized because poorly considered classroom delivery of their lessons can present challenges for Korean university students, resonating with a complex web of issues revolving around EFL learning in Korean society (i.e., Adams & Gottlieb, 2017;Ahn, 2011;Chun, Kim, Park, McDonald, Oh, Kim, & Lee, 2017;Song, 2013;Thompson & Lee, 2018).…”
Section: Textbooks and Efl Education In Korean Contextsmentioning
confidence: 99%
“…Although the ZPC framework is designed to be suitable for any expanding circle culture with EFL programs, we will look closely at Korean post-secondary contexts because of the vignette that demonstrates the use of the framework "in situ." For Korean students, much like EFL students elsewhere, learning English is a socioeconomic investment and an attractive commitment to political stakeholders involved with post-secondary education policy at the national level (Ahn, 2011;Canagarajah, 2016;Song, 2013). However, some university EFL programs promote a language learning curriculum that 1) inhibit creative or spontaneous expression, 2) deny student involvement as informative to the syllabus, and 3) adhere to seemingly antiquated methodological or theoretically established principles that overlook any other language learning phenomenon (Paik, 2018;Stoller, 2015).…”
Section: Textbooks and Efl Education In Korean Contextsmentioning
confidence: 99%
“…Scholarship presented on ELT in South Korea has historically been expressed from a binary aspect of native speaker versus nonnative speaker or “Western” culture versus “non‐Western” culture (Ahn, ; Cook, ; Holliday, , ), in which the characteristics of the individual teacher, except nationality, become unknown and/or disregarded; the default is presumed White. The dictions White and Western are typically used interchangeably and reinforce an ideal NES (Cook, ; Holliday, , ).…”
Section: Revisiting the Native Speakermentioning
confidence: 99%